2008
DOI: 10.1007/s10750-008-9481-2
|View full text |Cite
|
Sign up to set email alerts
|

Identifying essential fish habitat for small pelagic species in Spanish Mediterranean waters

Abstract: Populations of small pelagic fish support important fisheries in Spanish Mediterranean waters, particularly sardine (Sardina pilchardus) and anchovy (Engraulis encrasicolus), and are distributed along the entire length of the Spanish continental shelf. Using annual acoustic survey data for the years 2003-2005, a GIS-based environmental modelling approach was used to investigate the distribution and abundance of small pelagic fish in relation to environmental variables. Multivariate analysis was applied to prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
38
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 28 publications
2
38
0
Order By: Relevance
“…Though both areas are productive (Bellido et al 2008), the chlorophyll and primary production values in the Alboran Sea are higher than those in the Delta zone (Siokou-Frangou et al 2010, Lazzari et al 2012, Salgado and Lorenzo 2014. By contrast, the surface temperature is lower in Alboran Sea than in the Ebro Delta area, although the main trend in both areas is an increasing temperature (Shaltout and Omstedt 2014) .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Though both areas are productive (Bellido et al 2008), the chlorophyll and primary production values in the Alboran Sea are higher than those in the Delta zone (Siokou-Frangou et al 2010, Lazzari et al 2012, Salgado and Lorenzo 2014. By contrast, the surface temperature is lower in Alboran Sea than in the Ebro Delta area, although the main trend in both areas is an increasing temperature (Shaltout and Omstedt 2014) .…”
Section: Discussionmentioning
confidence: 87%
“…The study of the degree of well-being of the anchovy population based on the condition factor index (Kn) proposed by Le Cren (1951) revealed that anchovy individuals in GSA01 were not only larger in length, but also had a greater weight for a given length than the anchovy in GSA06. Both the Ebro Delta (GSA06) and the Alboran Sea (GSA01) are essential habitats for anchovy due to their productive conditions (Bellido et al 2008). However, the enrichment process differs: in the Alboran Sea nutrient enrichment comes mainly from coastal upwelling (Agostini andBakun 2002, Mercado et al 2013), whereas in the Ebro Delta area it comes via the transport of nutrients from the Gulf of Lions and the turbulent mixture occurs as a result of the discharge of nutrient-rich fresh water coming from the Ebro River (Salat 1996, Agostini andBakun 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of this, they have been largely used in the Mediterranean Sea (e.g. Martín et al 2008, Bellido et al 2008, Giannoulaki et al 2013. A variant of the GAM is the threshold GAM (TGAMs, Ciannelli et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…The areas of higher probability of juvenile presence were located in coastal shallow zones (40-41°N and 9°W~Aveiro and 38°N and 9.6°W~south of Sado River in the west; area covering the Gulf of Cadiz in the south), similarly to what is found in the Mediterranean Sea. In this area, suitable sardine nursery areas are presumably located in shallow coastal waters (up to 100 m depth) in the north of the Alboran Sea, the Sicily Strait, the western coast of the Italian Peninsula, and the Cretan Shelf in Greek seas, and areas along the Levantine coast (, and the Cretan Shelf in Greek seas, and areas along the Levantine coast (Bellido et al 2008, Giannoulaki et al 2011. This reinforces the hypothesis of juveniles' preference for areas with plenty of food and physical protection.…”
Section: Discussionmentioning
confidence: 99%